Designing Urban Food Policies Concepts and Approaches - Brand, Caroline; Bricas, Nicolas; Conaré, Damien; Daviron, Benoit; Debru, Julie; Michel, Laura; Soulard, Christophe-Toussaint (Urban Agriculture,, 2019)
This Open Access book is for scientists and experts who work on urban food policies. It provides a conceptual framework for understanding the urban food system sustainability and how it can be tackled by local governments. Written by a collective of researchers, this book describes the existing conceptual frameworks for an analysis of urban food policies, at the crossroads of the concepts of food system and sustainable city. It provides a basis for identifying research questions related to urban local government initiatives in the North and South. It is the result of work carried out within Agropolis International within the framework of the Sustainable Urban Food Systems program and an action research carried out in support of Montpellier Méditerranée Métropole for the construction of its agroecological and food policy.